Tracking control of nonholonomic mobile agents with external disturbances and input delay. (May 2018) - Jenabzadeh, Ahmadreza; Safarinejadian, Behrouz
Abstract: This paper investigates the tracking control problem of chained-form nonholonomic multiagent systems (MASs). In contrast to the existing works in which some algorithms have been designed for ideal conditions, the destructive factors including external disturbances and input delay are considered in the dynamics of the agents in this work. Two distributed controllers are proposed such that the states of the controlled agents can track the states of the target in the presence of external disturbances and input delay. For this purpose, a distributed controller is firstly suggested based on a switching method to solve the tracking control problem for nonholonomic MASs with external disturbances. Then, the proposed control law is extended based on a state predictor for the tracking control of agents in the presence of input delay. The stability analysis of the two distributed controllers is also provided. Simulation results show the promising performance of the proposed algorithms. Graphical abstract: Highlights: The finite-time tracking control problem is solved for chained-form nonholonomic multi-agent systems in this paper. The results are extended for multi-agent systems with external disturbances and input delay. A novel state predictor is proposed to predict future states of the chained-form nonholonomic systems in a finite-time. The stability of the proposed algorithms is also analyzed based on the Lyapunov stability theory.